Psychometric Properties of the Jordanian Version of the Irrational Procrastination Scale among a Sample of the University of Jordan Students and the Extent of its Prevalence during the COVID-19 Pandemic - Nofal , Mohamed Bakr (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to verify psychometric properties of the Jordanian version from the irrational procrastination scale and the extent of its prevalence among a sample of the University of Jordan students. Methods: The descriptive survey has been used. The irrational procrastination scale has been applied to a sample of 286 participants, 86 males, 200 females chosen by the simple random method. The face and construct validity have been verified using the exploratory factor analysis method. The reliability coefficient has been extracted by Cronbach's alpha and Split half reliability. Results: Findings show the presence of two factors; commitment to perform tasks and delay. Orthogonal rotation process (Varimax) was applied on these two factors. The percentage of total variance explained by these two factors was (50.349%). The reliability of the scale verified using Cronbach’s alpha coefficient of internal consistency ranged between (0.684) for first factor and (0.634) for second factor, while it reached (0.657) for the scale. While the split-half reliability ranged between (0.634) and (0.686), and for the total degree (0.542). Regarding the extent of irrational procrastination among students at the University of Jordan, it was (3.11) for first factor, and (3.01) for second factor and it was a medium value. It also reached (3.07) for the scale as a whole and it was a medium value too. Conclusion: The study recommends that the irrational procrastination scale has a reliable degree of psychometric properties on a sample of university students, which indicates its validity in measuring irrational procrastination behavior.